The Social and Emotional Lives of Overweight, Obese, and Severely Obese Children. Issue 5 (25th May 2016) - Harrist, Amanda W.; Swindle, Taren M.; Hubbs‐Tait, Laura; Topham, Glade L.; Shriver, Lenka H.; Page, Melanie C.
Abstract : This study examines inter‐ and intrapersonal problems associated with being overweight among one thousand one hundred sixty‐four 6‐ to 7‐year‐olds (49% boys) in 29 rural schools. Socioemotional data include child self‐reports, peer sociometrics, and teacher reports. Results support the hypothesis that children with weight problems struggle socially and emotionally, and extend current understanding of child obesity by demonstrating that problems appear early, are evident in a community sample, can be identified using standard sociometric methods, and are worse among children with severe obesity. Sociometric status difference between levels of obesity were also found. Although obese children were neglected by peers, severely obese children were rejected.